Regulatory Obstacles and Small, Micro and Medium-sized Enterprises - Worku, Zeleke (International Review of Management and Marketing, 2019)
The study was conducted in order to assess and evaluate factors that affect the ease of borrowing money by small, micro and medium-sized enterprises (SMMEs) from microfinance agencies and commercial banks in Pretoria West. The study was conducted by drawing a stratified random sample of size 334 SMMEs that conduct business in Pretoria West. Data was collected by using a structured, pretested and validated questionnaire of study. The degree of entrepreneurial skills of respondents was assessed by using a composite index developed by Choto et al.(2014). Data analyses were conducted by using methods such as frequency tables, cross-tab analyses and ordered logit analysis. The study found that 23.65% of SMMEs were granted loans needed for business operation, whereas the remaining 76.35% of businesses were not granted loans needed for business operation. Based on odds ratios estimated from ordered logit analysis, the ability of business operators to secure loans from money lending institutions was significantly influenced by 3 factors. These factors were level of entrepreneurial skills, ability to order merchandise in bulk on credit from wholesale suppliers and distributors, and participation in social capital activities. Keywords: Pretoria West, SMME, Access to loan, Entrepreneurial skills, Odds ratio JEL Classifications: M13, M21, D21, R38 DOI: https://doi.org/10.32479/irmm.8088